Pengaruh Knowledge Management dan Pengembangan Sumber Daya Manusia terhadap Kinerja Karyawan PDAM Kota Padang - Alfian Alfian; Deslita Taileleu (Lembaga Yasin AlSys, 2026)
Studies on the factors influencing employee performance have been widely conducted, but research that specifically examines the role of knowledge management and human resource development in the public service sector remains relatively limited. This study aims to analyze the effect of knowledge management and human resource development on the employee performance of PDAM Kota Padang. This study used a quantitative approach with a survey design, involving 90 respondents selected through the total sampling technique. Data were collected using questionnaires and analyzed with multiple linear regression after validity, reliability, and classical assumption tests assisted by SPSS. The results showed that knowledge management and human resource development had a positive and significant effect on employee performance. These findings reinforce the concept of human resource management, which emphasizes the importance of knowledge management and competency improvement within organizations. The conclusion of this study confirms that both factors are key elements in improving employee performance and therefore need to receive serious attention from management. The implications of this study include a practical contribution for organizations in designing more effective employee development strategies, as well as opening opportunities for further research by incorporating other relevant variables.